Nest defense behavior against the attack of ants in colonies of pre-emergent Mischocyttarus cerberus (hymenoptera, vespidae) - Togni, Olga Coutinho [UNESP]; Giannotti, Edilberto [UNESP] (My University, 2007)
The study was carried out at the UNESP Rio Claro campus (SP), where biotests consisting of simulated ant attacks were performed in colonies of Mischocyttarus cerberus. The behaviors of the wasps were recorded with a camcorder, for further analysis. This analysis was done using the Mann-Whitney U test and the Principal Component Analysis. In the pre-emergence development stage, colonies with a single foundress defend the nest only after the first larvae appear. When there are only eggs in the nest, the wasp abandons the nest. Before leaving, the wasp rubs its gaster against the nest, releasing the ant repellent secretion. When the nest contains larvae or larvae and pupae, the foundress defends the colony, vibrating its wings, pumping her abdomen and biting the ant.
Keywords: Ants; Defense of nest; Mischocyttarus cerberus; Pre-emergence stage; Formicidae; Hymenoptera; Mischocyttarus; Vespidae